What is new in the treatment surgical hemorrhoids? - Vivas, Carlos (Cirugía del Uruguay, 2003)
The critica! revision of the literature on surgical treatment of hemorrhoidal pathology has as main purpose the analysis of clinical efficiency of recently introduced technologies and hence it is lirnited to that wich has been published within the last two years. So as to avoid introducing bias into the qualitative analysis, only randornized and controlled series are taken into account. In order to facilitate evaluation of the efficiency of each procedure, series are gropued according to their indication and results are compared according to the new techniques. The evaluation concludes with recommendations regarding therapy which evolve from the evidence analyzed.